Moroccans', Ecuadorians' and Romanians' assimilation in Spain - Núria Rodríguez-Planas; Raquel Vegas (Institute for the Study of Labor (IZA), 2012)
Using the 2007 Encuesta Nacional de Immigración (ENI), we find that male migrants follow a similar labor and legal assimilation pattern in Spain regardless of their nationality (with Romanians faring worse in terms of legal status but better in terms of employment status at arrival). Among women, Moroccans and Ecuadorians follow a similar pattern that contrasts with the one observed among Romanian women. While the former mainly arrive to Spain to work with legal status and with time in Spain (some of them) move out of employment, the latter are considerably (and persistently) more attached to the labor force, although they tend to lack legal status at arrival, and only gain such status overtime. Controlling for observable characteristics and using Heckman-corrected estimates, our wage analysis finds that with the exception of Moroccan and Romanian males for which no wage differences are observed, Moroccans outperform the other two nationalities in terms of higher wages at arrival. Moreover, this wage differential does not decrease over time.
Keywords: J15; J24; J61; J62; 330; legal and employment assimilation; Southern and Eastern Mediterranean men and women; Marokkaner; Rumänen; Südamerikaner; Geschlecht; Soziale Integration; Berufliche Integration; Spanien